Multi-walled carbon nanotube dispersion by the adsorbed humic acids with different chemical structures. (January 2015) - Zhang, Di; Pan, Bo; Cook, Robert L.; Xing, Baoshan
Abstract: Dissolved humic acid (disHA) is effective for suspending carbon nanotubes (CNTs), but the suspending mechanism is still unclear. This study used bleached and hydrolyzed humic acids as suspending agents to investigate effects of chemical structures on CNTs suspension. The adsorption of aromatic moieties-enriched disHA to CNTs was lower than aliphatic components-enriched disHA, but the former was better at suspending CNTs. These findings led to the development of a model, in which disHA with aromatic structures results in stable suspension of CNTs due to stronger steric hindrance. Because of their flexible structures, aliphatic components-enriched disHA molecules easily conformed to CNTs leading to higher adsorption to CNTs but weaker steric hindrance between CNTs. Therefore, the bridging and less suspension of CNTs was observed. This study emphasizes that suspending CNTs by disHA is not only controlled by the adsorbed amount of disHA, but also the chemical nature of disHA. Graphical abstract: Highlights: Bleaching increases the aliphaticity of humic acids. The aliphatic moieties-rich disHA was favorable to adsorb on CNTs. The aromatic moieties-rich disHA was better at suspending CNTs. The steric hindrance of disHA controlled the suspension of CNTs. Abstract : Aliphatic-enriched disHA showed higher sorption to CNTs but aromatic-enriched disHA displayed better dispersibility.